Likelihood of Environmental Contamination of Patient Rooms in Six Acute Care Facilities based on Facility, Unit-Type, and Precautions Status. (4th October 2017) - Tanner, Windy; Zhang, Yue; Leecaster, Molly; Stratford, Kristina; Mayer, Jeanmarie; Croft, Lindsay D; Alhmidi, Heba; Cadnum, Jennifer; Jencson, Annette; Koganti, Srilatha; Piedrahita, Christina; Donskey, Curtis J; et al.
Abstract: Background: Environmental contamination may play a critical role in ARO (antibiotic-resistant organism) transmission. The objective of this study was to estimate facility-unit contamination in 6 healthcare facilities and determine if differences existed among facilities, unit types, and room contact precautions status. Methods: In each facility, two units with patients with a recent positive test of a target ARO (MRSA, VRE, or carbapenem-resistant Gram-negatives in the previous 6 months or C. difficile in the previous 30 days) were randomly selected every 2 weeks for 8 cycles. Within units, surfaces were sampled in all contact precautions rooms of patients with a target ARO, 1–2 randomly selected non-contact precautions rooms per contact precautions room, and the nursing station. Multilevel logistic regression was used to model the association of facility, unit type and room type with risk of contamination. The inverse of sampling probability was used as weights in the regression. Results: A total of 196 ARO contact precautions rooms and 221 non-precautions rooms were sampled from 24 units (9 ICUs; 13 acute care medicine/surgical units; 2 transplant units) totaling 1, 448 specimens. Of 417 rooms sampled, 23% were positive for one or more of the target AROs. Fourteen percent of non-precautions rooms were positive for target AROs, and 17% of ARO precautions rooms were positive for AROs other than the known target ARO. In general, prevalence of environmental ARO contamination did not differ between facilities sampled. Compared with ICUs, odds of contamination on transplant and acute care units were 5.86 and 3.85 times higher, respectively. Non-precautions rooms and nursing stations were significantly less likely to be contaminated with AROs compared with contact precautions rooms (OR = 0.24, P < 0.001) and (OR = 0.34, P = 0.009), respectively. Conclusion: Detection of target AROs in non-precautions rooms and at nursing stations suggests colonized patients may be going undetected, cleaning is not sufficiently removing contamination from prior ARO patients, or AROs are being transferred from infected patients to other locations within the unit. Additional intensive sampling may further illuminate priority areas for interventions within acute care facilities. Disclosures: All authors: No reported disclosures.